2021
DOI: 10.1002/cche.10394
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of mycotoxigenic fungi on shelled corn using selective infrared heating technique

Abstract: Mycotoxigenic fungal contamination of corn poses significant health-related risks to consumers (Shad and Atungulu, 2017; Atungulu et al., 2018). The most prevalent mycotoxins that contaminate corn in the United States include aflatoxins, fumonisins, and deoxynivalenol (Abbas et al., 2002; Mohammadi Shad et al., 2019b; Robens & Cardwell, 2003; Wu et al., 2011). Chauhan et al. (2016) conducted a study on fungal infection, and aflatoxin contamination in corn collected from the Gedeo zone in Ethiopia and found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
(55 reference statements)
1
11
0
Order By: Relevance
“…This is in accordance with the study of Bowie et al (2019) and Wilson et al (2020) when rice and corn were exposed to different IR wavelengths, respectively. There was a complete aflatoxigenic mold inactivation when the sample was treated with IR intensity of 15.71 and 10.08 kW/m 2 for 20 and 30 s. Also, complete aflatoxigenic mold inactivation was observed using IR intensity of 7.27 kW/m 2 for 30 s. Hamanaka et al (2011) reported about 90% inactivation of a mold (Cladosporium) when exposed to IR heat for 120 s. The sample…”
Section: Effect Of Selected and Broadband Ir Wavelength Treatments On Sample Aflatoxigenic Mold Loadsupporting
confidence: 93%
“…This is in accordance with the study of Bowie et al (2019) and Wilson et al (2020) when rice and corn were exposed to different IR wavelengths, respectively. There was a complete aflatoxigenic mold inactivation when the sample was treated with IR intensity of 15.71 and 10.08 kW/m 2 for 20 and 30 s. Also, complete aflatoxigenic mold inactivation was observed using IR intensity of 7.27 kW/m 2 for 30 s. Hamanaka et al (2011) reported about 90% inactivation of a mold (Cladosporium) when exposed to IR heat for 120 s. The sample…”
Section: Effect Of Selected and Broadband Ir Wavelength Treatments On Sample Aflatoxigenic Mold Loadsupporting
confidence: 93%
“…The chemical and microbial contamination of food and feedstuff products poses threats such as a shortened shelf life and negative health effects depending on the contamination rates and overall toxicity of the contaminants. In the past, different decontamination strategies were developed to treat contaminated crops [ 1 , 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…IR wavelengths are grouped into near‐infrared (0.75–1.4 μm), mid‐infrared (1.4–8 μm), and far‐infrared (8–1000 μm) (Krishnamurthy et al, 2008). A ceramic IR emitter has been used to generate three selected wavelengths (3.2, 4.5, and 5.8 μm), which fall in the mid‐infrared region (Wilson et al, 2021). Since the IR heating technique supplies a high heat flux to the surface of the grain during drying and microbial inactivation, the quality of grain including color and pasting properties may be affected.…”
Section: Introductionmentioning
confidence: 99%
“…IR wavelengths are grouped into near-infrared (0.75-1.4 μm), mid-infrared (1.4-8 μm), and far-infrared (8-1000 μm) (Krishnamurthy et al, 2008). A ceramic IR emitter has been used to generate three selected wavelengths (3.2, 4.5, and 5.8 μm), which fall in the mid-infrared region (Wilson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation